Exclusive breastfeeding and its impact on neurodevelopment - Alghamdi, Saeed Salem; Alruwaili, Mansour Sultan; Alruwaili, Mansour Sultan; Alanazi, Nafea Hamoud; Alanazi, Nafea Hamoud; Alalmaei, Abdulaziz Zaher; Alalmaei, Abdulaziz Zaher; Alshammari, Rashed Sattam; Alshammari, Rashed Sattam; Tuwalah, Faisal Fahad Bin; Tuwalah, Faisal Fahad Bin; Alqahtani, Abdullah Saif; et al. (International Journal Of Community Medicine And Public Health, 2021)
Many advantages have been reported among the various studies in the literature about the efficacy of breastfeeding on brain development, which is mainly attributable to the abundant presence of the bioactive compounds and the essential fatty acids in breast milk. Moreover, it has been proven that breastfeeding enhanced long-term outcomes in children. In this context, arachidonic acid and docosahexaenoic acid are two fatty acids that were previously reported to be associated with the developmental outcomes of the retina, nerve cells and brain. Both of these amino acids have also been found in breast milk, and they are not present in other milk formulas as cow’s milk which is usually administered to newborns. In the present literature review, we aim to discuss the impact of exclusive breastfeeding on neurodevelopment. The findings from various studies indicate the strong effect of breastfeeding on the neurodevelopmental outcomes as compared to the administration of other milk formulas. Another finding from previous literature, the favorable events that are obtained from breastfeeding were also found to be sustained to the school-age of these children. On the other hand, evidence regarding the efficacy of breastfeeding on brain development in preterm infants is still poor. As a result, further studies are needed to furtherly validate this point. The main mechanisms by which favorable neurodevelopmental outcomes are obtained following breastfeeding are the nutritional values that are found within the breast milk along with the physical interactions between the mothers and infants during breastfeeding.